Analysis of IT Infrastructure Readiness and System Integration Capabilities in Improving Tax Reporting Data Reliability in Fintech Start-ups in Indonesia - Loso Judijanto; Mega Arum; Andi Hasryningsih Asfar; Junet Kaswoto; Heny Fitriani; Eko Sudarmanto (West Science Interdisciplinary Studies, 2026)
This study aims to analyze the effect of IT infrastructure readiness and system integration capability on the reliability of tax reporting data in fintech startups in Indonesia. The research employs a quantitative approach using primary data collected from 35 respondents through structured questionnaires measured on a Likert scale. Data analysis was conducted using IBM SPSS Statistics, including descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that IT infrastructure readiness has a positive and significant effect on the reliability of tax reporting data, demonstrating that stable, secure, and scalable systems contribute to improved data accuracy and consistency. Similarly, system integration capability shows a significant positive influence, highlighting the importance of seamless data flow and interoperability among organizational systems in minimizing errors and inconsistencies in reporting. Simultaneously, both variables significantly affect tax reporting reliability, with a coefficient of determination (R²) of 0.642, indicating that 64.2% of the variance in tax reporting reliability can be explained by these factors. The findings suggest that fintech startups need to strengthen both their IT infrastructure and system integration to enhance compliance, transparency, and data reliability in tax reporting processes. This study contributes to the literature by providing empirical evidence on the role of technological capabilities in supporting reliable tax reporting within digital financial ecosystems.